National Identity without Intellectual Bases: Israel’s Practical Zionism in Developing a State for the Jews - Hidayat, Syahrul (UI Scholars Hub, 2015)
Israel as a state has been existing for almost 70 years. Despite of decades of its pres¬ence, the foundation and its struggle for survival and acknowledgement have been constantly challenged including from its own supposedly the backbone of its Israel national identity: intellectuals. This paper argues that the critics from some of Jew¬ish intellectuals represent the fundamental problem of the effort to build a national identity. If nationalism, especially in European context as its birthplace, was usually supported by the intellectuals as the source of imagination of bounded group, the case of Israel shows different direction, at least problematic. Two prominent Jewish intel¬lectuals, Martin Buber and Hannah Arendt, presented here are the examples of the challenge against Jewish domination on Israel nationalism. Although they did not wish to disconnect their identity as Jews and agreed with an authoritative political institution to protect the Jews both were against the idea of Jewish domination and annihilation of Palestinians. As their views were against the principles of pragmatism, lack of at¬tention and support from the Zionist political leaders has made their intellectual ideas relatively isolated from the mass.